2007
DOI: 10.1111/j.1524-4725.2007.33171.x
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy for High-Risk Nonmelanoma Skin Cancers

Abstract: Compared to melanoma, SCC of the skin are much less predictable as regards their tendency to metastasize to the regional lymph nodes. Although the SLNB appears to be a reliable staging procedure for NMSC (especially SCC), the yield may be too low to justify its routine use in this patient population. More data are needed to determine when a SLNB is justified in the management of NMSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 33 publications
0
29
0
1
Order By: Relevance
“…In six patients (35%) a negative SLN was thus not associated with a good prognosis, resulting in a low sensitivity for SLNB in cSCCs. In the literature, some studies have shown no false-negative SLNs, 11,20 whereas others had a rate of false-negative SLNBs around 10% 23,24 or 33%. 10 Also, rates for positive SLNs vary from 0% 23 to over 4Á5% 22 up to 44%.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In six patients (35%) a negative SLN was thus not associated with a good prognosis, resulting in a low sensitivity for SLNB in cSCCs. In the literature, some studies have shown no false-negative SLNs, 11,20 whereas others had a rate of false-negative SLNBs around 10% 23,24 or 33%. 10 Also, rates for positive SLNs vary from 0% 23 to over 4Á5% 22 up to 44%.…”
Section: Discussionmentioning
confidence: 98%
“…26 However, other groups have defined a false-negative result as a tumourfree SLNB with metastatic disease at any body site. 23 Using the first, stricter, definition we had one of 17 patients with a false-negative SLN (6%). However, five more patients developed metastatic disease at distant body sites despite a negative SLN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemical stains adipophilin and perilipin for the identification of lipid within specimens have proven to be useful. 5761 Experience with the use of SLN biopsy in sebaceous carcinoma with ocular 29,33,62 and extraocular 6365 involvement is limited. To date, SLN positivity rates range from 17% (2/12) 62 to 20% (1/5).…”
Section: Sebaceous Carcinoma Of the Eyelid And Conjunctivamentioning
confidence: 99%